Development of an Algorithm for Internet Marketing Strategy Implementation: A Case Study in the EU Hotel and Restaurant Sector - Kolisnychenko, Tetiana; Sefikhanova, Kateryna; Kapral, Olha; Karpenko, Vitalii; Sylkin, Oleksandr (Ingénierie des systèmes d'Information, 2023)
This article is dedicated to the development of an algorithm for the implementation readiness of an Internet marketing information technology strategy within the enterprise context, specifically focusing on the EU market's hotel and restaurant services sector. The research adopts modern quantitative assessment methods and constructs a multifactor correlation regression model as its core methodology. Statistical analyses have been conducted, leading to the formation of a multifactorial correlation and regression model, which underpins the development of the implementation readiness algorithm for the Internet marketing information technology strategy. The outcomes of this study comprehensively address the set objectives and tasks. The novelty lies in the proposed methodological approach for presenting the implementation readiness algorithm, offering an innovative perspective on constructing the algorithm for developing a marketing strategy. However, the study's applicability is limited, as it focuses on enterprises within the EU market with specific operational directions. Therefore, the effectiveness of the current model may be reduced when applied to enterprises outside the EU market or those with significantly different activities. Future research directions should consider adapting and expanding this methodology to other business sectors and markets beyond the EU, with a particular emphasis on its applicability in different segments of the IT sector.